Elementos institucionais e do campo organizacional do basquete brasileiro que influenciam a liga de basquete feminino - Bragagnollo, Renato Dupas (2016)
Institutional theory has returned to the scenario of management research in academia. The renaissance came with the trajectory of neoinstitutionalism, guided by the social bias that starts to approach the study of institutions with the outside look inside the organizations, considering its organizational field, its actors and the universe in which this institution is allotted. In the field of sports management studies, researchers at both the international and national levels use this theory to justify phenomena that occur with sports organizations. In this work, the study will be guided by the institutionalization of a sports entity of the universe of Brazilian basketball, the Women's Basketball League. Because this entity has undergone three distinct processes since its foundation, provoking successive organizational rearrangements, the research points out the influences of its organizational field, where interferences of the external and internal environments of the organization, provoke its incontinuity. The single case study used interviews with actors from the organizational field, analysis of documentary content and direct observation by the researcher. Among the results, it was observed that there was intention of the LBF to reproduce a pre-existing structure in the male basketball, which would characterize the phenomenon as mimetic isomorphism, but after analysis and discussion it was characterized as coercive isomorphism. In the transition from the first phase to the second phase of the process studied, the LBF suffered political and social pressures that resulted in the rearrangement of its structure, the second phase of transition characterized by interferences of political, social and functional pressures. On legitimacy, it is understood that the institution is recognized by its main leaders, the clubs, and needs to strengthen the relationship with society. The application of this study is reinforced by the social orientation of the neoinstitutionalism with the focus on the organizational field of Brazilian basketball. It is proposed as a managerial intervention the execution of sports projects aimed at the basketball community in partnership with clubs that participate in the LBF.